Pendekatan Interkultural terhadap Pembelajaran Bahasa Arab dalam Memahami Budaya Arab - Sofiatus Sobriyah (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
Technology gives students access to the vast and diverse world of Arab culture, and Arabic is a language rich in cultural values and customs. The significance of Arabic is increasing in the digital era due to its association with Islamic culture and Middle Eastern countries that have great political, economic and cultural influence. Therefore, it is very important for Arabic language learners to use intercultural learning to improve their Arabic language proficiency. The aim of this research is to investigate how the use of an intercultural approach in teaching Arabic affects students' understanding of Arab culture. Through observations, interviews, and examination of teaching materials, a qualitative case study design was used in this research. Study room. Research findings show that the intercultural approach in teaching Arabic has increased students' understanding of Arab culture and increased their enthusiasm for learning.